Talent is an All-Round, Extremely Powerful and Unique Ability (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the fact that talent is a well-developed, extremely powerful and unique ability. It is advisable to look for talented young people, give them sensible guidance, involve them in inclass and out-of-class activities and direct their abilities in specific areas.